Strategi Tim Sapu Bersih Pungutan Liar dalam Upaya Memberantas Pungutan Liar - Roly Ramanda (Faculty of Social Science, Universitas Negeri Padang, 2019)
This research is motivated by the existence of the problem of illegal levies carried out by the school against students who are not based on certain rules and not through an agreement between the school and parents or also referred to as Illegal Levies. The research was conducted to find out the strategy of the Team Saber Pungli Padang City in an effort to eradicate the education sector illegal fees in Padang City, as well as the obstacles faced and efforts to overcome these obstacles. The method used in this study is a qualitative approach using descriptive methods. The research informants were conducted purposively. The type of data used is primary data and secondary data with data collection techniques using source triangulation techniques. Then the data is analyzed through the stages of data reduction, data presentation, and conclusions / verification that are carried out during the research process. The results of the study can be concluded that the saber pungli team strategy in eradicating extortion there are several stages, namely: intelligence, prevention through socialization, action and justice. The researcher concluded that the Padang City illegal broom team team strategy had been implemented and for the results had begun optimally, as evidenced by the response from the community about no more illegal fees made by the school against students and reduced public reports of extortion in school. To be more optimal and the success of this strategy, it is better for the team to work together again with all government and community groups to jointly eradicate illegal fees.